Insegnanti con disabilità e DSA Dilemmi, sfide e opportunità - Bellacicco, Rosa; Ianes, Dario; Pavone, Marisa (Traiettorie inclusive, 2022)
The promotion of greater diversity in the socio-demographic profile of the teaching population is the subject of an increasing international interest. However, the perspective of teachers with disabilities/specific learning disorders (SLDs) is still poorly investigated, especially in Italy. The entry of teachers with disabilities/SLDs into the teaching profession can represent a decisive step towards the development of increasingly higher levels of inclusion both in teacher training and in the school setting, also considering the benefits that teachers with disabilities/SLDs can bring in terms of inclusive values and practices. Although, the topic raises some dilemmas and tensions, elicited by the dual mandate of schools and universities, which are called to ensure the quality of: a) the educational offer; b) the professional profile of (student) teachers who (will) work in schools. At the same time, they need to grant (student) teachers the right to use accommodations during their educational and professional career. The volume presents a multi-perspective reflection on the subject, presenting ‒ in particular ‒ two systematic reviews on international research on the topic and an empirical study conducted within the Italian context. The latter investigated the facets underlying the inclusion of (student) teachers with disabilities/SLDs through a multi-method approach.